Unity3D FPS TB CARE Game for Tuberculosis Awareness among Digital Native Children: Game TB CARE FPS Unity3D untuk Kesadaran Tuberkulosis pada Anak-anak Generasi Z - Pratiwi, Fahyu Dwi; Turusta, Cindy (Indonesian Journal of Innovation Studies, 2023)
The present study focuses on the development of the TB CARE game, with the aim of addressing the limited knowledge about tuberculosis (TB) in the community, particularly among children. Considering the digital native nature of generation Z, games are adopted as an appropriate medium for dissemination. Employing the observation method, specifically blackbox testing, the study evaluates the game's performance through tests and questionnaires. The findings indicate a significant success rate of approximately 93.5%, signifying the game's efficacy in accordance with the projected outcomes. The TB CARE game exhibits promising potential for future advancements in line with evolving science and technology Highlights: Development of engaging Unity3D FPS TB CARE game to address TB knowledge gap among children. Successful implementation of blackbox testing, with approximately 93.5% game feasibility. Promising potential for future advancements in line with evolving science and technology.